Up in the clouds : an environmental scan on cloud computing for micro, small and medium enterprises in the Philippines implications for future strategic prospectives - Araos, Rachelle R. (University of the Philippines Diliman, 2011)
This report is based upon technology foresight process on Cloud Computing for MSMEs in the Philippines. The report draws from various research papers, news articles, and international surveys conducted on Cloud Computing, ICT and MSMEs. A survey was also conducted in an attempt to analyze local MSMEs in the ICT/ICTE sector and those from other sectors. The Philippines ranks second among countries with most individuals owning a business. This is due to the fact that most Filipinos have an optimistic attitude towards entrepreneurship. Entrepreneurship is viewed as a vehicle for financial freedom, a glimmer of hope to quit employment and be one's own boss. These views partnered with the economic situation in the Philippines are enough to fuel a person's desire to start a business. The problem among MSMEs in the Philippines is that many businesses are offering the same or similar products and services. This tends to affirm the common notion that "the typical Filipino business person is risk-averse (segurista) and lacking in originality and innovation (gaya-gaya)." These attitudes can hinder them from exploiting new opportunities for growth and results in stiff competition among MSMEs. Apart from these, it was also noted in some studies that almost a quarter of Filipino entrepreneurs do not prioritize technology and tend to stick with the more traditional approaches which they used to start their businesses. New technologies and processes can provide MSMEs with better quality and productivity and improve the company's production efficiency. As a consequence, they can produce cheaper products with superior quality and thereby lead to higher business potential. Cloud computing has become a buzz word in the IT industry during the recent years. The increasing need of business for mobility and the fast-paced developments in online applications and connectivity are making Cloud Computing more and more appealing for businesses. However, due to the size of their data and applications, it would be a bigger challenge for large enterprises to adopt this model. The advantages of cloud technology such as reduced cost and IT management and maintenance, as well as increased business value, productivity and competitiveness can be leveraged better by MSMEs. The adoption and promotion of Cloud Computing in the Philippines is dependent on the improvement of our ICT infrastructure and power generation. Provided that Cloud Computing is heavily dependent on internet connection, the availability and reliability of ICT infrastructure is of utmost importance. The open competition in the telecommunications industry enables users to choose from a variety of service providers and services. However, despite of a number of telecommunications companies in the sector, internet continues to be available mostly in the metropolitan areas and not in more rural parts of the country. And if and when a connection is available outside the metro, the connection tends to be weak and unreliable. The same, sadly, is true for electricity. The availability of electricity continues to be a problem in areas outside metropolitan districts. This state of infrastructure and power generation does not help in imploring more MSMEs to adopt Cloud Computing or any technology for that matter. The survey that was conducted in aid of this study on four different companies in varying sectors yielded results that support the results of most international surveys and news articles. MSMEs in the Philippines are interested in Cloud Computing and most realize the advantages that it can provide their businesses. However, most of them would rather use the free cloud services while maintaining their own internal infrastructure. The fear of the security of their data while it sits on some server in the cloud has been the biggest impediment on the decision to embrace cloud computing fully in their organizations. This reminds me of the initial stages of the online banking system and ecommerce. The fear of exposing credit card numbers and bank account numbers was then the greatest impediment for individuals. Philippine MSMEs will in time adopt cloud computing. However, they will not be, in any way, early adopters of this technology. As with other technologies that came before, Filipino MSMEs will only jump into the wagon when it has gained enough ground and they have seen its success in many other businesses of their size.